The Term Structure of Interest Rates and Monetary Policy During a Zero-Interest-Rate Period - Nagayasu, Jun (IMF Working Papers; Working Paper ;, 2003)
This paper empirically evaluates the validity of the term structure of interest rates in a low-interest-rate environment. Applying a time-series method to high-frequency Japanese data, the term-structure model is found to be useful for economic analysis only when interest rates are high. When interest rates are low, the usefulness of the model declines, since the interest spread contains little information that can be used for predicting future economic activity. The term-structure relationship is also weakened by the Bank of Japan's use of interest rate smoothing.